MSMEs' Intention in Adopting Sharia Equity Crowdfunding: An Empirical Study Using TAM and TPB - Virgiawan, Rheyza; Nur, Sofyan Ashari; Nugroho, Rizal Bayu Bakti (Ekonomi Syariah IAIN Kudus, 2025)
This study attempts to explore the factors that influence MSMEs' decisions to adopt sharia equity crowdfunding (SECF) models in Indonesia by analyzing the integration of the theory acceptance model (TAM) and the theory of planned behavior (TPB) framework on Micro, Small, and Medium Enterprises (MSMEs) intention in using sharia equity crowdfunding. This quantitative study involved 695 MSMEs, utilizing an online questionnaire as the data collection method, which was subsequently analyzed using structural equation modeling (SEM) with Smart-PLS software. The study shows that MSMEs consider more aspects of convenience and benefits related to the technology offered by sharia equity crowdfunding. Additionally, subjective norm (SN), attitude (ATT), and PBC also play crucial roles. Interestingly, the interest of MSMEs in adopting sharia equity crowdfunding does not depend on the perception of others but instead prioritizes the direct experience they can perceive from sharia equity crowdfunding. Key findings include significant positive effects of Perceived Usefulness (PU) on ATT and ItU (Intention to Use), Perceived Ease of Use (PEU) on ItU and PBC, and SN on PU and PEU.